SHALAT SUBUH BERJAMA’AH DAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN AL MUBAROK, KAB. LINGGA. - Milasari; Suhardiman; Saleha (Miftahul Ulum, 2023)
Prayer is a worship that must be carried out by muslims to get closer to Allah SWT. If they do not pray, they are among the people who are disadvantage. Because it has an influence on those who carry out as a believer performs obligatory and sunnah prayers properly and correctly. Obeying the provisions of prayer, the pillars of harmony in prayer in paying attention to the conditions for the validity of prayer, they are among those who carry out amar ma’ruf nahi mungkar. This quantitative research aimed to examine the influence of congregational Fajr prayer on the discipline of students (santri) at Al Mubaarok Islamic Boarding School in Pulau Medang Village. Data was collected using observation, questionnaires, and documentation, and analyzed through percentage calculations and the product-moment correlation with SPSS 22. The results revealed that the performance of congregational Fajr prayer among the students was categorized as "good" (78%), while their discipline was considered "very good" (81%). The correlation coefficient between congregational Fajr prayer and student discipline was 0.457, indicating a moderate correlation. Overall, the study found a significant positive impact of congregational Fajr prayer on the discipline of students at Al Mubaarok Islamic Boarding School in Pulau Medang.